Your Pace or Mine: Culture, Time and Negotiation - MACDUFF, Ian (Institutional Knowledge at Singapore Management University, 2006)
This article explores the impact that different perceptions of time may have on cross-cultural negotiations. Beyond obvious issues of punctuality and timekeeping, differences may occur in the value placed on the uses of time and the priorities given to past, present, or future orientations. The role of time in negotiations involves two key dimensions: differing perceptions and values of time, and the management of time. Both dimensions, the author suggests, need to be on the negotiation table.